Weissella cibaria Attenuated LPS-Induced Dysfunction of Intestinal Epithelial Barrier in a Caco-2 Cell Monolayer Model - Huang, Liping; Cui, Kang; Mao, Wenhao; Du, Yurong; Yao, Ning; Li, Zhen; Zhao, Huan; Ma, Wang (Frontiers in Microbiology, 2020)
The dysfunction of intestinal epithelial barrier contributes to local or systemic infection and inflammation. Some lactic acid bacteria (LAB) strains had been shown to improve the conditions of barrier function and, for this reason, are recognized as probiotics. Weissella. cibaria, a species belonging to the LAB group, is known to promote several health benefits. However, the role of W. cibaria in regulating integrity of intestinal epithelial barrier has not yet been investigated. In this study, W. cibaria MW01 was isolated from Chinese sauerkraut and was selected based on its functional features, such as gastric juice and bile salts tolerance, besides antagonistic activity against pathogenic bacteria. In a cellular model of intestinal barrier, it was observed that W. cibaria was able to adhere more efficiently than Lactobacillus rhamnosus GG in Caco-2 cells. Moreover, the LPS-induced inflammation in Caco-2 cells was attenuated by the treatment with W. cibaria MW01, which reduced the synthesis of TNF-α, IL-6 and IL-8. In addition, it was noted that the treatment with W. cibaria MW01 recovered the integrity of Caco-2 cell monolayer exposed to LPS. Furthermore, W. cibaria MW01 significantly alleviated LPS-induced down-regulation of tight junction (TJ) proteins (Claudin, Occludin, and Tight junction protein-1). Mechanistically, W. cibaria MW01 inhibited the translocation of NF-κB to the nucleus and deactivated the MLCK-pMLC pathway during LPS exposure. Thus, W. cibaria MW01, as a potential probiotic, can protect intestinal epithelial barrier function by regulating inflammation and expression of TJ proteins via NF-κB-mediated MLCK-pMLC pathway.